Combination of Nebulizer and Active Cycle of Breathing Technique (ACBT) to Reduce Shortness of Breath in Asthma Patients - Tomayahu, Siti Ayulia; Siti Nadhir Ollin Norlinta; Yani, Fitri (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Asthma is a chronic inflammatory disorder of the airways that experiences continuous inflammation, causing increased airway hyperresponsiveness that causes symptoms of shortness of breath, chest heaviness, wheezing especially at night or during the day. The Word Health Organisation says there are currently 235 million asthma sufferers in the world. The Riskesdas survey results showed the highest prevalence of asthma in 2018 at 4.8%. DIY 3.5% and data from the Bantul district health office in 2018, asthma in Bantul district as many as 5,572 people. Methods: quantitative research with quasi-experimental methods. using pre test and post test one group design with a combination of Nebulizer and Active Cycle of Breathing Technique (ACBT). before and after treatment, the sample measured shortness of breath using the Borg Scale to determine the level of shortness of breath. Sampling using total sampling technique with sampling that uses all the population as a sample on the condition that it meets the inclusion and exclusion criteria. Results: based on the test results of the Wilxocon signed rank test obtained a sig value of p=0.000, namely the combination of Nebulizer and Active Cycle of Breathing Technique can reduce shortness of breath in asthmatics.Conclusion: data analysis shows a value of p=0.000 (p<0.05) indicating that there is an effect of the combination of Nebulizer and Active Cycle of Breathing Technique on reducing shortness of breath in asthmatics.